K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

16 tháng 2 2022

6x2−2xy=3y−11x+2

→2xy+3y=6x2+11x−2

→y(2x+3)=(6x2+9x)+(2x+3)−5

→y(2x+3)=3x(2x+3)+(2x+3)−5

→y=3x+1−52x+3

→5⋮2x+3

→2x+3∈{1,5,−1,−5}

→2x∈{−2,2,−4,−8}

→x∈{−1,1,−2,−4}

→y∈{−7,3,0,−10}

Chúc em học tốt

16 tháng 2 2022

Ta có :

\(6x^2-2x=3y-11x+2\)

\(\rightarrow2xy+3y=6x^2+11x-2\)

\(\rightarrow y\left(2x+3\right)=\left(6x^2+9x\right)+\left(2x+3\right)-5\)

\(\rightarrow y\left(2x+3\right)=3x\left(2x+3\right)+\left(2x+3\right)-5\)

\(\rightarrow y=3x+1-\dfrac{5}{2x+3}\)

\(\rightarrow5⋮2x+3\)

\(\rightarrow2x+3\in\left\{1,5,-1,-5\right\}\)

\(\rightarrow x\in\left\{-1;1;-2;-4\right\}\)

\(\rightarrow y\in\left\{-7,3,0,-10\right\}\)

11 tháng 9 2021

a) \(3x^2-6xy=3x\left(x-2y\right)\)

b) \(x^3-6x^2+9x=x\left(x^2-6x+9\right)=x\left(x-3\right)^2\)

c) \(=x\left(x-2y\right)-3\left(x-2y\right)=\left(x-2y\right)\left(x-3\right)\)

d) \(=2x\left(3x-5\right)-3\left(3x-5\right)=\left(3x-5\right)\left(2x-3\right)\)

11 tháng 9 2021

\(a,=3x\left(x-2y\right)\\ b,=x\left(x-3\right)^2\\ c,Sửa:x^2-2xy-3x+6y=x\left(x-2y\right)-3\left(x-2y\right)=\left(x-2y\right)\left(x-3\right)\\ d,=\left(3x-5\right)\left(2x-3\right)\)

24 tháng 11 2017

xem lại đề

25 tháng 11 2017

ko sai

8 tháng 7 2015

x2-7x+12

=x2-3x-4x+12

=x(x-3)-4(x-3)

=(x-3)(x-4)

x4-4x2+4x-1

=x4-1-4x2+4x

=(x2-1)(x2+1)-4x(x-1)

=(x-1)(x+1)(x2+1)-4x(x-1)

=(x-1)[(x+1)(x2+1)-4x]

=(x-1)(x3+x2+x+1-4x)

=(x-1)(x3+x2-3x+1)

6x4-11x2+3

=6x4-2x2-9x2+3

=2x2(3x2-1)-3(3x2-1)

=(3x2-1)(2x2-3)

 

3 tháng 8 2015

1) = [(x2 + x) + 4.(x2 + x) + 4] - 28   = (x2 + x + 2)2 - \(\left(\sqrt{28}\right)^2\) = (x+ x + 2 + \(\sqrt{28}\)). (x+ x + 2 - \(\sqrt{28}\))

2) = (x+y)2 - 3.(x + y) - 10  = [(x+y)2 - 5.(x + y)] + [2(x+y) - 10]

=  (x+y).(x+y-5) + 2.(x+y-5) = (x+y - 2). (x+y-5)

3) = 6x4 - 2x2 - 9x2 + 3 =  2x2. (3x- 1) - 3. (3x- 1) = (2x2 - 3).(3x2 -1)

21 tháng 8 2023

Bài 12:

a) \(\left(\dfrac{1}{2}x+4\right)^2\)

\(=\left(\dfrac{1}{2}x\right)^2+2\cdot\dfrac{1}{2}x\cdot4+4^2\)

\(=\dfrac{1}{4}x^2+4x+16\)

b) \(\left(7x-5y\right)^2\)

\(=\left(7x\right)^2-2\cdot7x\cdot5y+\left(5y\right)^2\)

\(=49x^2-70xy+25y^2\)

c) \(\left(6x^2+y^2\right)\left(y^2-6x^2\right)\)

\(=\left(y^2+6x^2\right)\left(y^2-6x^2\right)\)

\(=y^4-36x^4\)

d) \(\left(x+2y\right)^2\)

\(=x^2+2\cdot x\cdot2y+\left(2y\right)^2\)

\(=x^2+4xy+4y^2\)

e) \(\left(x-3y\right)\left(x+3y\right)\)

\(=x^2-\left(3y\right)^2\)

\(=x^2-9y^2\)

f) \(\left(5-x\right)^2\)

\(=5^2-2\cdot5\cdot x+x^2\)

\(=25-10x+x^2\)

21 tháng 8 2023

\(11,\)

\(a,\left(7x+4\right)^2-\left(7x+4\right)\left(7x-4\right)\)

\(=\left(7x+4\right)\left(7x+4-7x+4\right)\)

\(=\left(7x+4\right).8=56x+32\)

\(b,\left(x+2y\right)^2-6xy\left(x+2y\right)\)

\(=\left(x+2y\right)\left(x+2y-6xy\right)\)

1 tháng 10 2021

\(1,=4x^2-2x+18x-9=2x\left(x-2\right)+9\left(x-2\right)=\left(2x+9\right)\left(x-2\right)\\ 2,=6x^2+3x+4x+2=3x\left(2x+1\right)+2\left(2x+1\right)=\left(3x+2\right)\left(2x+1\right)\\ 3,=-\left(5x^2+4x+25x+20\right)=-\left[x\left(5x+4\right)+5\left(5x+4\right)\right]=-\left(x+5\right)\left(5x+4\right)\\ 4,=-\left(7x^2-14x+3x-6\right)=-\left[7x\left(x-2\right)+3\left(x-2\right)\right]=-\left(7x+3\right)\left(x-2\right)\\ =\left(7x+3\right)\left(2-x\right)\)

1 tháng 10 2021

thank

26 tháng 11 2020

các bn ơi

26 tháng 11 2020

a, \(3x^2-6xyz+3y^2z=3\left(x^2-2xyz+y^2z\right)\)

b, \(x^2-3x-y^2+3y=x^2-y^2-3x+3y=\left(x-y\right)\left(x+y\right)-3\left(x-y\right)\)

\(=\left(x-y\right)\left(x+y+3\right)\)

c, \(3x^2-11x+6=3x^2-9x-2x+6x\)

\(=x\left(3x-2\right)-3\left(3x-2\right)=\left(x-3\right)\left(3x-2\right)\)